The Effectiveness of Using Artificial Intelligence in Folk Tale Learning - Qoriana Kiki; Hary Soedarto; Priyanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The integration of artificial intelligence (AI) in folk tale learning represents a transformative educational approach, enhancing engagement, understanding, and accessibility. AI-driven platforms facilitate narrative comprehension by providing adaptive and interactive learning environments. Computational models of narrative ability enable AI systems to simulate human-like comprehension, adjusting storytelling elements based on learners' responses. Interactive storytelling tools further support language acquisition and critical thinking by allowing learners to influence narrative outcomes. Additionally, AI fosters inclusive education through accessibility features, such as audio descriptions and scaffolding strategies for diverse learners. AI-driven adaptive learning methodologies also enhance personalized learning experiences, catering to individual needs. Moreover, intelligent tutoring systems (ITS) provide real-time feedback, optimizing instructional strategies while allowing educators to focus on pedagogical development. By revolutionizing folk tale learning, AI enhances narrative engagement, supports second-language learning, and assists educators in instructional design. This study explores the effectiveness of AI in folk tale learning by analyzing engagement levels, comprehension improvements, and accessibility benefits. Findings suggest that AI enhances folk tale learning through personalized, interactive, and adaptive storytelling experiences, fostering greater learner participation and comprehension.